Probing hydrogen spillover in Pd@MIL-101(Cr) with a focus on hydrogen chemisorption - Szilagyi, Petra; Callini, E.; Anastasopol, A.; Kwakernaak, C.; Sachdeva, S.; van de Krol, R.; Geerlings, H.; Borgschulte, A.; Zuttel, A.; Dam, B. (R S C Publications, 2014)
Palladium nanoparticles can split the dihydrogen bond and produce atomic hydrogen. When the metal nanoparticles are in intimate contact with a hydrogen-atom host, chemisorption of H-atoms by the host has been suggested to occur via the hydrogen spillover mechanism. Metal–organic frameworks were predicted to be able to act as effective chemisorption sites, and increased ambient-temperature hydrogen adsorption was reported on several occasions. The intimate contact was supposedly ensured by the use of a carbon bridge. In this work, we show that it is possible to introduce catalyst palladium particles into MOF’s pores and simultaneously ensuring good contact, making the employment of the carbon bridge redundant. The addition of Pd nanoparticles indeed increases the ambient-temperaturehydrogen uptake of the framework, but this is found to be solely due to palladium hydride formation. In addition, we show that the hydrogen atoms do not chemisorb on the host framework, which excludes the possibility of hydrogen spillover.